Inventory of the Seaweeds and Seagrasses of the Hawaiian Islands - Alison R. Sherwood; Michael D. Guiry (Biology, 2023)
This updated list is composed of a total of 661 records, which includes 71 brown algae, 450 red algae, 137 green algae, and three seagrasses, with an overall rate of endemism of 13.2%. Almost half (46.7%) of the Hawaiian records presented here are represented by at least one DNA sequence, while 16.3% are confirmed through a DNA sequence match to a topotype, and 6.7% are confirmed through a DNA sequence match to a type specimen. The data are presented in the context of the natural history of the Hawaiian Islands, which is heavily influenced by the volcanic hotspot origin of the archipelago in the middle of the Pacific Ocean, as well as the important cultural role of seaweeds and other marine plants in Hawai‘i, and the current threats to marine ecosystems, which include the introduction and proliferation of a number of invasive marine macroalgae.